PERAN SISTEM KEUANGAN DESA (SISKEUDES) DALAM PENGELOLAAN DANA DESA DI DESA CINGAMBUL KECAMATAN CINGAMBUL KABUPATEN MAJALENGKA - diding bajuri; ujang permana (Jurnal Ilmu Administrasi CENDEKIA, 2022)
ABSTRACTThis research is based on the existence of problems, namely in the Role of the Village Financial System (Siskeudes) in the Management of Village Funds in Cingambul Village, Cingambul District, Majalengka Regency, it is still not optimal and effective, based on observations of these symptoms, it is suspected that the implementation of the village financial system (Siskeudes) has not been fully implemented in accordance with the prevailing Regulation of the Minister of Home Affairs.Given these problems, the authors are interested in conducting research whose results will be set forth in the form of a thesis entitled "ROLE OF THE VILLAGE FINANCIAL SYSTEM (SISKEUDES) IN MANAGEMENT OF VILLAGE FUNDS IN CINGAMBUL VILLAGE, CINGAMBUL DISTRICT, MAJALENGKA REGENCY".In the collection technique using descriptive method with a qualitative approach and accompanied by data collection techniques through observation, interviews, and documentation. The results of the research on the role of the village financial system (Siskeudes) in managing village funds in Cingambul Village, Cngambul District, Majalengka Regency by using the theory of system characteristics with a nine-dimensional approach with twelve indicators, namely having components, having boundaries, having an environment, having links/interfaces, having processing, having outputs, having goals and objectives, having control, having feedback (Edhy Sutanta) is the lack of cooperation in the village financial system (Siskeudes), there are technical and non-technical constraints on the application of the village financial system in managing village funds, there are still complaints from village apparatus in the village financial system (Siskeudes).